Analysis of the Effect of Regional Taxes and Regional Levies on Increasing Regional Original Revenues of North Sumatra for 2016-2021 - Jhoni Laris Simbolon; Khairul Syabirin Daulay; Sarah Claudya Nainggolan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of local taxes and regional levies on local revenue in North Sumatra. The population in this study is the entire data on local taxes, regional levies, and local revenue in North Sumatra. The research sample is data on local taxes, regional levies, and local revenue in North Sumatra from 2016 to 2021, namely for seven years. Data collection technique is documentation. Data analysis was carried out using multiple linear regression analysis, the data obtained was classified, tabulated and processed using Eviews Version 12. The results showed that local tax variables had a significant effect on regional original income in North Sumatra, while regional retribution variables had no significant effect on regional original income. in North Sumatra.